Treatment and Outcomes of Pancreatic Cancer in Armenia: A Retrospective Study From Resource-Limited Settings - Elen Baloyan; Davit Zohrabyan; Liana Safaryan; Armen Avagyan; Lilit Harutyunyan; Vardan Bardakhchyan; Jemma Arakelyan; Amalya Sargsyan; Martin Harutyunyan; Mariam Mailyan; Gevorg Tamamyan; Samvel Bardakhchyan (JCO Global Oncology)
PURPOSEPancreatic cancer is one of the deadliest cancers in the world. In Armenia, it is 12th by incidence. The aim of this study is to evaluate treatment and outcomes of pancreatic cancer in Armenia during the past 12 years.METHODSThis is a retrospective study with data from three oncology centers in Armenia: “Muratsan” Hospital of Yerevan State Medical University, Mikaelyan institute of surgery, and Yeolyan Hematology and Oncology Center. The information was obtained from the medical records of the patients with pancreatic cancer treated at these centers during January 1, 2010-January 1, 2022. Log-rank test and Kaplan-Meier curves were used for survival analysis. Cox regression analysis was performed for identification of main prognostic factors.RESULTSOf 70 patients involved in the final analysis, 45.7% was female. The median age at diagnosis was 63 years. The median follow-up time was 11 months (range, 2-146). A total of 11.4% of patients had stage I-II, 27.1% had stage III, and 60% had stage IV disease. The main independent prognostic factor for overall survival (OS) was the TNM stage, whereas grade of the tumor was not significant. The median OS was 11 months (range, 2-169 months): In stages I-III, patients who had surgery (44.4%) lived significantly longer than those who did not (20 v 11 months; P = .008). Main chemotherapy regimens were 5-fluorouracil, oxaliplatin, folinic acid and irinotecan (41.4%) and gemcitabine plus capecitabine (38.6%). No significant survival difference was found between these groups (13 v 11 months; P = .162).CONCLUSIONSurvival of patients with pancreatic cancer in Armenia is dismal, not exceeding 1 year. Hopefully, further research in the field and new treatment modalities will improve the situation.